Budidaya Sarang Burung Walet Untuk Peningkatan Ekonomi Masyarakat Desa Kalora Poso Pesisir Utara - Afandy, Zaidan; Nugroho, Moh Agus (Jeksyah: Islamic Economics Journal, 2021)
Swallow's nest cultivation business has prospects to be developed due to the high demand for swallow's nest. This profit is a source of additional income for the community in Kalora Village, Poso Pesisir Utara District. This type of research uses quantitative descriptive analysis with tabulation analysis methods, which are then presented in tabular form and interpretation of respondents' answers in this study. Based on the results of this study, it shows that between swallow nest cultivation and the community's economy, including the level of the relationship is quite strong. This shows that there is a reciprocal relationship and it can be said that swallow nest cultivation has a positive effect on the economy of the community, so these results also indicate that swallow nest cultivation is influenced by several variable factors. Cultivation of swallow's nest has a significant effect on the economy of the community. Thus the cultivation of swallow's nest helps and improves the economic welfare of the community.